Orientasi Pembentukan Koalisi dan Fragmentasi Kepentingan dalam Penentuan Calon Wakil Bupati Ende Sisa Masa Jabatan 2019-2023 - Leda, Helenerius Ajo (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
This article aims to describe the orientation of forming a coalition of parties supporting the MJ Package in the 2018 Pilkada, the rivalry of the coalition party elites when fighting for the position of Deputy Regent of Ende, along with the various political interests behind the rivalry that occurred. In order to approach this problem, references to the theory and concept of the Office-seeking coalition are used. This study uses a qualitative descriptive research method. Research data was collected through interviews, documentation, triangulation and analyzed qualitatively. The results of this study conclude that the orientation of the coalition formed in the MJ Package winning coalition in the 2018 Pilkada is an office-seeking coalition that tends to be pragmatic, considering the electability and popularity of the candidates. Coalitions in the form of office seeking create coalition configurations that are easily fragile, fragmented and conflictual, as evidenced by the differences in attitudes and political interests in determining the candidates for Deputy Regent of Ende for the remainder of the 2019-2023 term. The elite battle behind differences in elite attitudes occurs because political party elites are not a single, apolitical entity but are fragmented into various interest factions both internally and externally.